Net Income Aggregation, Investor Inattention, and Portfolio Holding Decisions: Evidence from the Insurance Industry - Amornsiripanitch, Natee; Goldstein, Brandon; Huang, Zeqiong; Kwon, David; Lin, Jinjie (The Review of Corporate Finance Studies, 2025)
Abstract This paper uses an accounting rule change and the U.S. insurance industry to empirically show that the way in which accounting information is presented can distort equilibrium economic outcomes. When firms’ summary performance measure includes changes in unrealized gains and losses (UGL) from financial asset holdings, investor inattention causes the firms’ stock returns to overreact to changes in UGL. Inattentive investors perceive the firms’ earnings as having higher residual uncertainty and demand larger discounts on the firms’ stock prices. To maximize compensation, managers cut financial asset holdings. Managerial myopia exacerbates the response. A simple model formalizes the mechanism. (JEL: G11, G14, G22, G30, M41)